Respuesta :
Answer:
Step-by-step explanation:
sin(2x) = 2 sin(x) cos(x) cos(2x) = cos2(x) – sin2(x) = 1 – 2 sin2(x) = 2 cos2(x) – 1. Now I am not sure if this is right but I remember another similar formula. Here is the correct formula cot x = cos x / sin x
2 ) ( sin² x + cos² x ) / cos x = sec x
1/cos x = sec x
sec x = sec x
cos² x + sin² x = 1
Step-by-step explanation:
[tex] \frac{ \ {sin}^{2} x + { \cos}^{2} x}{cos \: x} = sec \: x \\ \\ LHS \\ = \frac{ \ {sin}^{2} x + { \cos}^{2} x}{cos \: x} \\ \\ = \frac{ 1}{cos \: x} \:( \because \: \ {sin}^{2} x + { \cos}^{2} x = 1) \\ \\ = sec \: x \\ = RHS \\ [/tex]